STUDI KUALITATIF PERAWATAN KELUARGA PASIEN HIPERTENSI DI DUSUN SUMBER DESA SEBAUNG GENDING PROBOLINGGO - Eka Diah Kartiningrum; Auli Ningtyas (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Hypertension is a high-risk of heart, nerve, kidneys, and vessels diseases. This study aimed to describe nursing care to the family of hypertension patient through comprehensive nursing approach. The method used a case study approach that used the family of hypertension clients in the developmental stages of teenage to old age and left - incomplete family development by the medical center. According to the case studies found that health management problems were ineffective (lack of knowledge of diet) related to the inability to care for sick family members. To Mrs. H’s family found health care problems to be ineffective (dependence on amlodipine 5 mg) associated with the inability to care for sick family members. The implementation of nursing care consists of higher concern for family hypertension, greater concern for diet, prevention, healthy lifestyle, stress management, and the ability to care well for sick family members.